2020
DOI: 10.1002/cssc.201903427
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Electron Densities of Ni‐N‐C Complexes by Hybrid Coordination for Efficient Electrocatalytic CO2 Reduction

Abstract: Metal‐N‐C is a type of attractive electrocatalyst for efficient CO2 reduction to CO. Because of the ambiguity in their atomic structures, the active sites and catalytic mechanisms of the catalysts have remained under debate. Here, the effects of N and C hybrid coordination on the activity of Ni‐N‐C catalysts were investigated, combining theoretical and experimental methods. The theoretical calculations revealed that N and C hybrid coordination greatly enhanced the capability of single‐atom Ni active sites to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…Such durability was much better than Ni@NC/NCNT, Ni@NC and NCNT (Figure S7c and d). More importantly, our catalyst surpassed most state‐of‐the‐art CO‐selective catalysts in terms of long‐term durability in CO 2 RR (Figure 4f and Table S7) [16,17,19,26,33–35,37,60,66,67,69,72,76–94] . These unambiguously demonstrated the advantage of the dual chainmail structure in reinforcing the catalyst and boosting the CO 2 RR performance.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Such durability was much better than Ni@NC/NCNT, Ni@NC and NCNT (Figure S7c and d). More importantly, our catalyst surpassed most state‐of‐the‐art CO‐selective catalysts in terms of long‐term durability in CO 2 RR (Figure 4f and Table S7) [16,17,19,26,33–35,37,60,66,67,69,72,76–94] . These unambiguously demonstrated the advantage of the dual chainmail structure in reinforcing the catalyst and boosting the CO 2 RR performance.…”
Section: Resultsmentioning
confidence: 60%
“…The results here further proved the lower energy barrier and thus higher activity of Ni@NC@NCNT towards CO 2 RR to produce CO. Moreover, the specific value of 118 mV dec −1 revealed that the rate‐determining step for Ni@NC/NCNT was the initial electron transfer process to form CO 2 .− or the concerted electron‐proton process to form * COOH [32,80–82] . To further determine whether a proton participated in the rate‐determining step, the reaction order of CO 2 RR with respect to bicarbonate was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental data corroborated the theoretical predictions, since Ni-N-C materials containing mixed N/C coordination synthesized at intermediate carbonization temperatures provided the best results in terms of activity and selectivity towards CO production. 320 Interestingly, the coordinative motif of Ni-N 2 C 2 moieties homogeneously dispersed on a 2D graphene layer shows structural analogies with an efficient homogeneous Ni catalyst bearing a macrocyclic ligand based on a redox-active 2,2 0 -bipyridyl core and electron-rich N-heterocyclic carbene (NHC) donors , previously discussed in the Section 4.2. 258 In particular, the optimal 15-membered macrocyclic configuration forced the molecular Ni system 54-Ni to a distorted square-planar arrangement which is consistent with synchrothron-based experimental data on analogous Ni-N 2 C 2 SACs.…”
Section: Ni-n-c Catalystsmentioning
confidence: 90%
“…258 In particular, the optimal 15-membered macrocyclic configuration forced the molecular Ni system 54-Ni to a distorted square-planar arrangement which is consistent with synchrothron-based experimental data on analogous Ni-N 2 C 2 SACs. 320 For the molecular Ni derivative 54-Ni, the contribution of the quasi-planar ligand environment to extra-electron delocalization revealed to be decisive to prevent the formation of a metal-hydride species.…”
Section: Ni-n-c Catalystsmentioning
confidence: 96%
See 1 more Smart Citation